Using pre-commitment to reduce alcohol consumption: Lessons from a quasi-experiment in Thailand. (June 2020) - Witvorapong, Nopphol; Watanapongvanich, Somtip
Abstract: Based on primary data of 453 drinkers in Thailand, this study investigates the impact of pre-commitment on alcohol consumption. It exploits the quasi-experimental nature of a social marketing campaign in Thailand implemented in 2014, where all drinkers were able to publicly pledge temporary alcohol abstention, and some but not all drinkers were provided with community-based health promotion interventions conducted by local residents. This study argues that the campaign had a pre-commitment device implicitly integrated into it; failures to follow through with the commitment were associated with mental costs of social embarrassment and weaker relationships with one's local social networks. Using a joint estimation method where the decision to pre-commit is explicitly endogenized, this study suggests that pre-commitment is effective in increasing the probabilities of temporary alcohol abstention and reduction. Highlights: We study the impact of pre-commitment on alcohol consumption. We exploit the quasi-experimental nature of a Thai alcohol-control campaign. The campaign encourages drinkers to pre-commit to temporary alcohol abstention. The pre-commitment increases the probability of alcohol abstention by 27.6%. Pre-commitment is most effective when combined with community interventions.